2014
DOI: 10.1371/journal.pone.0091745
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B Virus Induces Cell Proliferation via HBx-Induced microRNA-21 in Hepatocellular Carcinoma by Targeting Programmed Cell Death Protein4 (PDCD4) and Phosphatase and Tensin Homologue (PTEN)

Abstract: Hepatitis B viral infection-induced hepatocellular carcinoma is one of the major problems in the developing countries. One of the HBV proteins, HBx, modulates the host cell machinery via several mechanisms. In this study we hypothesized that HBV enhances cell proliferation via HBx-induced microRNA-21 in hepatocellular carcinoma. HBx gene was over-expressed, and miRNA-21 expression and cell proliferation were measured in Huh 7 and Hep G2 cells. miRNA-21 was over-expressed in these cells, cell proliferation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
54
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(63 citation statements)
references
References 36 publications
6
54
0
Order By: Relevance
“…miRNA-21 is an anti-apoptotic gene that has an important role in the mechanism of anti-apoptosis and the regulation of programmed cell death factor 4 (PDCD4). In addition, miRNA-21 is able to reduce myocardial cell death after H 2 O 2 stimulation via regulation of PDCD4 (23). Furthermore, myocardial ischemia may induce damage to myocardial cells via miRNA expression (24).…”
Section: Discussionmentioning
confidence: 99%
“…miRNA-21 is an anti-apoptotic gene that has an important role in the mechanism of anti-apoptosis and the regulation of programmed cell death factor 4 (PDCD4). In addition, miRNA-21 is able to reduce myocardial cell death after H 2 O 2 stimulation via regulation of PDCD4 (23). Furthermore, myocardial ischemia may induce damage to myocardial cells via miRNA expression (24).…”
Section: Discussionmentioning
confidence: 99%
“…Most of these miRs have not been earlier reported in context of acute liver failure, but have been reported in hepatocellular carcinoma [28], insulin resistance [29], leukemia [30], breast cancer [31], and prostate cancer. Only, two miR-504 and miR-374c had been reported to be upregulated in mice with acute liver failure-induced hepatic encephalopathy [32] and HBV related acute on chronic liver failure [23]. In animal models of drug induced ALF (drug/DGalN/LPS) different miRs from our study like miR-15b, 16, 197, 122 and 221 were expressed [8, 9, 11].…”
Section: Discussionmentioning
confidence: 63%
“…Additionally, miR- 627, 651 and 877 reglaute cancer cell proliferation by modulating processes like apoptosis and cell cycle progression [19, 20, 21]. miRs related to HEV infection significantly lead to the upregulation of BIRC3 and PDCD4 genes, which have also been implicated in cell death in hepatitis B virus infection [22, 23]. …”
Section: Discussionmentioning
confidence: 99%
“…24 lncRNA tumour suppressor candidate 7 also acts as a miR-211 sponge to inhibit colorectal cancer cell proliferation by down-regulating CDK6. Some reports have illustrated that the HBx protein-induced miRNA expression also shares association with the carcinogenic network of HCC, [39][40][41] but whether the aberrantly up-regulated miR-211-5p in HCC is directly induced by HBx protein still needed to be investigated. Later, we also observed that miR-211-5p inhibition brought about the same inhibitory effects on HCC cells as lncRNA F11-AS1 overexpression.…”
Section: Discussionmentioning
confidence: 99%